1998
DOI: 10.1007/s004210050449
|View full text |Cite
|
Sign up to set email alerts
|

Training decreases muscle glycogen turnover during exercise

Abstract: The present study was undertaken to determine the effects of endurance training on glycogen kinetics during exercise. A new model describing glycogen kinetics was applied to quantitate the rates of synthesis and degradation of glycogen. Trained and untrained rats were infused with a 25% glucose solution with 6-3H-glucose and U-14C-lactate at 1.5 and 0.5 microCi x min(-1) (where 1 Ci=3.7 x 10(10) Bq), respectively, during rest (30 min) and exercise (60 min). Blood samples were taken at 10-min intervals starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Even when faced with an exogenous glucose infusion [final concentration 25% (w/w)], both trained and untrained rats experience significant hepatic glycogenolysis during exercise (Azevedo et al, 1998). In our study, although all three phenotypes showed a net glycogenesis in liver from 16:00 h to 07:00 h (Table 2), there was a negative relationship between the number of revolutions at 02:00 h and glycogen concentration in liver (Fig.…”
Section: Glycogen Concentration and Circadian Patternsmentioning
confidence: 50%
See 1 more Smart Citation
“…Even when faced with an exogenous glucose infusion [final concentration 25% (w/w)], both trained and untrained rats experience significant hepatic glycogenolysis during exercise (Azevedo et al, 1998). In our study, although all three phenotypes showed a net glycogenesis in liver from 16:00 h to 07:00 h (Table 2), there was a negative relationship between the number of revolutions at 02:00 h and glycogen concentration in liver (Fig.…”
Section: Glycogen Concentration and Circadian Patternsmentioning
confidence: 50%
“…Moreover, the observed increase in [glycogen] from 16:00 h to 07:00 h (particularly evident for liver of all mice, for gastrocnemius of HR normal and for soleus of HR mini; Table 2) implies that a net glycogen deposition occurs concomitantly with the period of active wheel running in these mice. Although the classic theory of glycogen metabolism is that complete activation of glycogen phosphorylase through phosphorylation is coupled with the complete inactivation of glycogen synthase (Stryer, 1995), several studies of glycogen kinetics in vivo have shown that simultaneous glycogen synthesis and degradation occurs both in liver and muscle during exercise in rats (Constable et al, 1984;David et al, 1990;Azevedo et al, 1998) and humans (Magnusson et al, 1994;Price et al, 1994).…”
Section: Glycogen Concentration and Circadian Patternsmentioning
confidence: 99%
“…Increase in glycogen consumption has been related to elevated fatigue (Ren et al 2011). By contrast, increase in fatty acid metabolism during exercise, leads to a decreased glycogen depletion rate and enhanced endurance exercise performance (Azevedo et al 1998;Favier & Koubi 1988). The enhanced availability of free fatty acids is thought to cause greater fat mobilisation in the active muscles (Oh & Ohta 2003).…”
Section: Discussionmentioning
confidence: 99%
“…15) Therefore, increased fatty acid utilization is thought to be important for endurance performance. These increases are associated with enhanced lipolysis and sparing of stored glycogen, resulting in a delay of complete glycogen depletion by increasing circulating catecholamines.…”
Section: Discussionmentioning
confidence: 99%